Estratégia de investimento público nas unidades de conservação federais de proteção integral - Cordeiro, Larissa Moraes (2018)
Applied ecology professionals must deal with de interface between the society and government when dealing with environmental issues. We are living in an environmental crisis that is related to high rates of global biodiversity loss. We tried to deepen the discussion of public policies that deal with the distribution of the federal budget in the largest system of protected areas in the world. The law nº9.985/2000 (SNUC) regulate the Brazilian Conservation Units, however, it lacks guidelines that deal with the federal budget. Therefore, in this work we assessed how the budget distribution was distributed to the Federal Conservation Units of strict protection between 2008 and 2016 according to already established conservation guidelines. The selected conservation guideline from SNUC were: richness of Extinction-threatened species, Biome, Units Category, Management Plan, Advisory Board and legal property of conservation unit land. Our results showed that the federal budget distribution is heterogeneous over time and units. This description gave support for discussion about which strategy should be adapted to perform this public investment. There is a necessity to implement a normative with legal guideline for the distribution of federal budget that takes into consideration de conservation guideline already established. We highlight the importance of professionals of environmental research to participate in legal decision-making space in order to rise legal guideline that establish a budget distribution that take into consideration the conservation guideline already established in law.